KEMAMPUAN LITERASI INFORMASI SISWA TENTANG APOTEK HIDUP BERBASIS INDIVIDUAL COMPETENCE FRAMEWORK (Studi Terhadap Siswa SMA di Kota Bandung) - Rully Khairul Anwar; Edwin Rizal; Encang Saepudin (Universitas Padjadjaran, 2015)
The availability of medicinal plants of the family as the pharmacy life has many used and increasing its use by the community. Increasing the utilization of herbal medicines and medicinal plants cause scientific information related to drugs have important position to become the scientific basis by the public and the company as well as a reference to